An Introduction to the Naiads of the Lake Texoma Region, Oklahoma, With Notes on the Red River Fauna (Mollusca: Unionidae) - Barry Dean Valentine; David Honor Stansbery (Hello World!, 1971)
The naiad fauna of the Oklahoma and tributaries of the Red River is treated, with particular reference to the 17 genera and 24 species of the Lake Texoma region. There are brief discussions of field and laboratory procedures, shell and soft part morphology, subfamilies of Unionidae, a summary review of U.S. genera based on soft anatomy, and a shell key to the 24 species of the region. Genera and species are briefly described, distinguished from similar taxa in the Red River, and discussed in terms of size, range, distribution, nomenclatorial problems, taxonomic problems and when pertinent, historical changes and ecology.